Securing the future of Hainan’s Tropical Rainforest: challenges and strategies for conservation - Shijie Wang; Chunping Xie (Frontiers in Forests and Global Change)
The Hainan’s Tropical Rainforest is China’s largest and best-preserved tropical rainforest, holding critical biodiversity value in the Indo-Burma biodiversity hotspot. Established as the Hainan Tropical Rainforest National Park (HTRNP) in 2021, it encompasses 95% of the island’s rainforest, safeguarding numerous endemic and protected species, including the endangered Hainan gibbon. Despite its ecological significance, the park faces severe anthropogenic threats, including deforestation driven by agricultural expansion, illegal mining, and hydropower development. These activities fragment habitats, disrupt species movement, and degrade essential ecosystem services such as water regulation and carbon sequestration. This commentary examines the current challenges to the park’s integrity and proposes a multifaceted conservation approach, focusing on strengthened enforcement, community engagement, policy implementation, and scientific monitoring. We advocate for a technology-driven enforcement system, sustainable livelihoods for local communities, and restoration of ecological connectivity to ensure the long-term protection of this invaluable ecosystem. Immediate and comprehensive action is crucial to preserve Hainan’s Tropical Rainforest as a global biodiversity treasure.